Histopathological Study of Placenta in Intrauterine Fetal Death: A Comprehensive Study from A Tertiary Institution - Suksham Sharma; Suby Singh (Dr. Annil Mahajan, 2023)
Background: Intra-uterine fetal death (IUFD) is the term used to describe the death of a foetus that is >24 weeks gestational age and/or >500 g in weight. The intricate process of fetal mortality involves the mother, the fetus, and the placenta; therefore, these issues should be handled together. Methods: This study was carried out in the Department of Gynaecology, GMC Jammu in collaboration with Department of Pathology w.e.f. March 2021 to October 2021. A total of 114 patients with intra-uterine fetal deaths diagnosed either through ultrasound reports or on clinical examination by absence of fetal heart sound were included in the study. The study comprised placentas from all cases of intrauterine fetal deaths with gestational ages greater than 28 weeks that were received in the histopathology section of the hospital. Results: Majority of IUFD patients accounting for (73.7%) had (28-36) weeks of gestational age. In majority of patients, the cause of IUFD was maternal (68.4%). PIH etiology was present in (55.1%), maternal anemia was evident in 21.7%, GDM was found in 11.5% patients. Majority of patients had calcification (54.4%), followed by 37.7% with infarct finding. Perivillous fibrin was present in 65.8%, followed by syncytial knots (46.5%), intervillous haemorrhage (43.9%). Conclusion: The morphology of the placenta can be further studied comprehensively to learn more about pregnancy anomalies, so that an optimal strategy can be developed concerning pregnancy management and risk assessment and even preventing IUFD in subsequent pregnancies.